A-hunting we will go! - Kellogg, Steven (New York : Morrow Junior Books, 1998)
In this modern version of the children$1 (Bs song, preparations for bedtime include "A-reading we will go, Now to the bath we go! Now off to bed we go!" Printed music on lining papers.s
Keywords: Children$1 (Bs songss -- Texts; Hunting -- Songs and music; Bedtime -- Songs and music; Songs